Atmospheric Advection and Precipitation Control Fog's Occurrence Over the Southern Ocean in Summer - Jiang, Keyue; Liu, Changwei; Yang, Qinghua; Vihma, Timo; Chen, Dake; Han, Bo (John Wiley & Sons, 2025)
Sea fog strongly affects human activities in the Southern Ocean (SO), but little is known about the factors controlling its occurrence and properties. Using multi-year ship-based observations and state-of-the-art atmospheric reanalysis data, we summarize two methods to identify sea fog episodes on a climatologic scale and estimate the sea fog occurrence in SO from 1979 to 2019. The first method considers the sea-air temperature difference and atmospheric humidity, while the second explores the similarity between fog and low-level clouds. Both methods revealed three centers of sea fog occurrence in the SO. Further analysis shows that the downward surface sensible heat flux due to the southward heat advection in the lower troposphere determines the monthly climatology and linear trends of sea fog occurrence. Precipitation suppresses summer sea fog over the entire SO and partly determines the latter's response to the Southern Annular Mode on an interannual scale.